SITENAR CERYA as an Innovation in English Language Learning at SMP Stella Matutina Salatiga: Merging Technology and Folktales - Englishtina, Inti; Putranti, Honorata Rarnawati Dwi; Danang, Danang; B Pujiati, Agnes Agnesita (Institut Teknologi Nasional, Bandung, 2024)
This study investigates the integration of SITENAR CERYA as an innovative approach to enhancing English language learning at SMP Stella Matutina Salatiga. SITENAR CERYA combines traditional folktales with modern technology to create an interactive learning experience. Employing qualitative implementation methods, including interviews, focus groups, and classroom observations, this activity examines participants' perceptions and experiences with SITENAR CERYA. The evaluation revealed that 85% of students reported increased engagement with English learning, and 90% of teachers noted a significant improvement in students' cultural appreciation and language acquisition. Furthermore, quizzes conducted during the activity showed an average 20% increase in students' language proficiency. These findings highlight the effectiveness of merging cultural heritage with technology in educational settings, offering valuable implications for future language teaching practices.